Catastrophic antiphospholipid syndrome in a patient with severe and refractory immune thrombocytopenic purpura: A case report - Farias, Milka Bríngel Batista; Hass, Rayssa Martins Souza; Batista, Thiago Naranjo; Passos, Luiz Fernando de Souza; Carneiro, Juliana Brandão Pinto; Carneiro, Barbara Seabra (Revista ft, 2026)
Background: Catastrophic Antiphospholipid Syndrome (CAPS) is a rare but life-threatening manifestation of Antiphospholipid Syndrome (APS), characterized by rapidly progressive multi-organ thrombosis and a mortality rate exceeding 40%. Its coexistence with refractory Immune Thrombocytopenic Purpura (ITP) creates an exceptionally complex clinical scenario defined by simultaneous hemorrhagic and thrombotic risks, with management directed at correcting thrombocytopenia to permit safe anticoagulation while implementing preventive antithrombotic measures during the interim period.Case Presentation: We report a case of severe refractory ITP in a 39-year-old female with confirmed APS who subsequently developed a CAPS event involving peripheral, pulmonary, and central vascular territories, despite multiple lines of escalating immunosuppressive therapy, thrombopoietin receptor agonist use, and splenic embolization.Discussion: Management requires the simultaneous pursuit of two clinical imperatives: correcting platelet counts to permit safe anticoagulation and implementing antithrombotic prophylaxis during the interval in which anticoagulation cannot be safely instituted. Treatment of thrombocytopenia escalates through corticosteroids and intravenous immunoglobulin (IVIG) as first-line agents, followed by immunosuppressants and thrombopoietin receptor agonists (TPO-RAs) as second-line options; procedural interventions are reserved for refractory cases. In catastrophic situations, combined therapy comprising full anticoagulation (whenever feasible), pulse corticosteroid therapy, and plasmapheresis and/or IVIG constitutes the standard of care. Importantly, TPO-RAs carry a recognized thrombotic risk in patients with pre-existing hypercoagulable states, as demonstrated in this case.Conclusion: The CAPS/refractory ITP association illustrates the boundaries of current therapeutic strategies. Even with aggressive, multidisciplinary, and coordinated interventions, clinical response may remain limited, reinforcing the need for novel therapeutic approaches to this complex autoimmune condition.